Progress in developing an infant and child feeding index: an example using the Ethiopia Demographic and Health Survey 2000 - Arimond, Mary; Ruel, Marie T. (2002)
Feeding practices are an important determinant of the nutritional status of infants and children. It is therefore useful to measure and describe infant and child feeding practices in a number of contexts. Such measurements could enable (1) international comparisons of the adequacy of infant and child feeding, (2) research linking infant and child feeding to determinants or outcomes, (3) advocacy regarding the importance of adequate infant and child feeding, and (4) monitoring and evaluation of interventions designed to change practices. This paper reports on progress in developing a summary measure of infant and child feeding practices—the infant and child feeding index (ICFI). The report also addresses two challenges in measuring child feeding practices, namely that infant and child feeding is multi-dimensional, and appropriate practices vary by age of the child. The authors refine the ICFI and confirm earlier findings that the ICFI is associated with child nutritional status. They also determine which components of the feeding index appear to be most important in driving its association with child nutritional status. Finally, they assess the potential usefulness of the index for the four purposes listed above.""---from Authors' Abstract